Crop nutrition & fertilization management of selected tropical fruit crops and tropical industrial tree crops - Magat, Severino S. (Philippine Council for Agriculture, Forestry and Natural Resources Reseach and Development, 2005)
This CD-ROM contains the PDF format of the book.